The Signaling Pathway of the ADP Receptor P2Y12 in the Immune System: Recent Discoveries and New Challenges - Entsie, Philomena; Kang, Ying; Amoafo, Emmanuel Boadi; Schöneberg, Torsten; Liverani, Elisabetta (International journal of molecular sciences, 2023)
P2Y12 is a G-protein-coupled receptor that is activated upon ADP binding. Considering its well-established role in platelet activation, blocking P2Y12 has been used as a therapeutic strategy for antiplatelet aggregation in cardiovascular disease patients. However, receptor studies have shown that P2Y12 is functionally expressed not only in platelets and the microglia but also in other cells of the immune system, such as in monocytes, dendritic cells, and T lymphocytes. As a result, studies were carried out investigating whether therapies targeting P2Y12 could also ameliorate inflammatory conditions, such as sepsis, rheumatoid arthritis, neuroinflammation, cancer, COVID-19, atherosclerosis, and diabetes-associated inflammation in animal models and human subjects. This review reports what is known about the expression of P2Y12 in the cells of the immune system and the effect of P2Y12 activation and/or inhibition in inflammatory conditions. Lastly, we will discuss the major problems and challenges in studying this receptor and provide insights on how they can be overcome.